Rheumatology Research Foundation Clinician Scholar Educator Award: Fifteen Years Promoting Rheumatology Educators and Education. Issue 11 (1st October 2016) - Berman, Jessica R.; O'Rourke, Kenneth S.; Kolasinski, Sharon L.; Aizer, Juliet; Wheatley, Mary J.; Battistone, Michael J.; Siaton, Bernadette C.; Criscione‐Schreiber, Lisa; Pillinger, Michael H.; Lazaro, Deana M.
Abstract : Objective: The Rheumatology Research Foundation's Clinician Scholar Educator (CSE) award is a 3‐year career development award supporting medical education research while providing opportunities for mentorship and collaboration. Our objective was to document the individual and institutional impact of the award since its inception, as well as its promise to strengthen the subspecialty of rheumatology. Methods: All 60 CSE Award recipients were surveyed periodically. Fifty‐six of those 60 awardees (90%) responded to requests for survey information that included post‐award activities, promotions, and further funding. Data were also collected from yearly written progress reports for each grant. Results: Of the total CSE recipients to date, 48 of 60 (80%) are adult rheumatologists, 11 of 60 (18%) are pediatric rheumatologists, and 1 is an adult and pediatric rheumatologist. Two‐thirds of survey respondents spend up to 30% of their total time in educational activities, and one‐third spend greater than 30%. Thirty‐one of the 60 CSE recipients (52%) have published a total of 86 medical education papers. Twenty‐six of 52 (50%) had received an academic promotion following the award. Eleven awardees earned advanced degrees. Conclusion: We describe the creation and evolution of a grant program from a medical subspecialty society foundation and the impact on producing education research, individual identity formation, and ongoing support for educators. This community of rheumatology scholar educators now serves as an important resource at the national level for the American College of Rheumatology and its membership. We believe that this grant may serve as a model for other medical societies that want to promote education scholarship and leadership within their specialties.